The Hallé, 1858-1983 : A History of the Orchestra - Kennedy, Michael 1926-2014 (Manchester Dover Manchester University Press, 1982)
"The Hallé, 1858-1983" by Michael Kennedy offers a meticulously researched chronicle of one of Britain’s foremost orchestras, tracking the pivotal developments in its musical journey over a span of more than a century. Kennedy deftly weaves together historical context, nuanced biographical sketches of key figures, and critical analyses of repertoire, illustrating how the Hallé Orchestra has served as both a vessel of cultural expression and a reflection of societal changes in the UK. The narrative is enriched by detailed accounts of landmark performances and the evolving dynamics of its conductors and musicians, making it an essential text for those who seek to understand the interplay between orchestral music and the broader artistic landscape. In its combination of scholarly rigor and accessible prose, Kennedy not only pays homage to the orchestra's legacy but also positions it within the continuum of musical innovation and tradition.
Includes index.
Bibliography: p. 140.
Keywords: Hallé Orchestra (Manchester, United Kingdom); 19th Century (1801-1900); 20th Century (1901-2000); Music history; Orchestra; Manchester (United Kingdom)